Competitive Microcredit Markets: Differentiation and ex-ante Incentives for Multiple Borrowing - Paolo Casini (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2010)
We analyze an oligopolistic microcredit market characterized by asymmetric infirmation and institutions that can offer only one type of contract. We study the effects of competition on contract choice when small entrepreneurs can borrow from more than one institution due to the absence of credit bureaus. We show that appropriate contract design can eliminate the ex-ante incentives for multiple borrowing. Moreover, when the market is still largely unserved and particularly risky, a screening strategy leading to contract differentiation and credit rationing is unambiguously the most effective to avoid multiple borrowing.
Keywords: G21; L13; L31; O16; 330; Microfinance; Competition; Credit Bureaus; Multiple Borrowing; Credit Rationing; Mikrofinanzierung; Informeller Finanzsektor; Kreditrationierung; Verhandlungstheorie; Unvollkommener Wettbewerb; Asymmetrische Information